Identification of single nucleotide polymorphisms on the D-loop region of mtDNA in Sundanese population - Wolly Candramila; Sony Heru Sumarsono; Bambang Suryobroto; Maelita Ramdani Moeis (Tropical Genetics, 2021)
Identification of sequence polymorphism on the D-loop region of mtDNA has been done for various purposes, including health and medical treatment. In this research, single nucleotide polymorphisms were identified in the D-loop region of mtDNA of the Sundanese population in western Java. A total of 118 unrelated and healthy Sundanese probands were collected from closed-traditional kampung adat and open communities distributed in 14 cities and regencies in western Java. DNA amplification and direct sequencing of the D-loop region were proceeded using primers L15990 and H409. Multi-alignment was conducted not only intrapopulation but also with D-loop sequence data stored in GenBank for comparison. In this research, we categorized high-frequency SNPs as less effective for identification in population studies because of their presence in other populations outside Indonesia. Meanwhile, lower-frequency SNPs showed typical variants of Sundanese haplotypes. On the other hand, rare or low-frequency SNPs should be re-examined in larger size of samples to have a better understanding of risk factors for many diseases.